Design and Construction of Aroyl‐Hydrazone Derivatives: Synthesis, Crystal Structure, Molecular Docking and Their Biological Activities. Issue 11 (25th October 2019) - Kumari, Pratibha; Ansari, Shagufi Naz; Kumar, Ravi; Saini, Anoop Kumar; Mobin, Shaikh M.
Abstract: Here, we report the synthesis and characterization of four new aroyl‐hydrazone derivatives L1 –L4, and their structural as well as biological activities have been explored. In addition to docking with bovine serum albumin (BSA) and duplex DNA, the experimental results demonstrate the effective binding of L1 –L4 with BSA protein and calf thymus DNA (ct‐DNA) which is in agreement with the docking results. Further biological activities of L1 –L4 have been examined through molecular docking with different proteins which are involved in the propagation of viral or cancer diseases. L1 shows best binding affinity with influenza A virus polymerase PB2 subunit (2VY7) with binding energy −11.42 kcal/mol and inhibition constant 4.23 nm, whereas L2 strongly bind with the hepatitis C virus NS5B polymerase (2WCX) with binding energy −10.47 kcal/mol and inhibition constant 21.06 nm . Ligand L3 binds strongly with TGF‐beta receptor 1 (3FAA) and L4 with cancer‐related EphA2 protein kinases (1MQB) with binding energy −10.61 kcal/mol, −10.02 kcal/mol and inhibition constant 16.67 nm and 45.41 nm, respectively. The binding energies of L1 –L4 are comparable with binding energies of their proven inhibitors. L1, L3 and L4 can be considered as both 3FAA and 1MQB dual targeting anticancer agents, while L1 and L3 are both 2VY7 and 2WCX dual targeting antiviral agents. On the other side, L2 and L4 target only one virus related target (2WCX). Furthermore, the geometry optimizations of L1 –L4 were performed via density functional theory (DFT). Moreover, all four ligands (L1 –L4 ) were characterized by NMR, FT‐IR, ESI‐MS, elemental analysis and their molecular structures were validated by single crystal X‐ray diffraction studies. Abstract :